Physiology and growth of maize under salinity of water and application of hydrogen peroxide - Francisco H. D. Lacerda; Francisco H. F. Pereira; Francisco de A. da Silva; Fabio M. de Queiroga; Marcos E. B. Brito; Joyce E. de Medeiros; Mirandy dos S. Dias (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The salinity of irrigation water or soil is the abiotic factor that most negatively impacts the yield of crops, including green maize, so it is necessary to find alternatives to ensure production. In this context, this study aimed to evaluate gas exchange, photosynthetic pigments, and growth of maize under salinity of irrigation water and application of hydrogen peroxide. The experiment was conducted at the Center of Sciences and Agrifood Technology, Pombal, PB, belonging to the Federal University of Campina Grande, in the period from January to February 2015, using the maize hybrid ‘AG 1051’. The treatments consisted of two salinity levels of irrigation water (0.3 and 2.0 dS m-1) and five concentrations of hydrogen peroxide (0, 40, 80, 160, and 320 µmol L-1) applied via irrigation water. The experimental design was completely randomized, in a 2 × 5 factorial scheme, with four replicates. ECw of 2.0 dS m-1 reduces transpiration, stomatal conductance, total chlorophyll, carotenoids, and initial growth, but does not affect the dry mass accumulation of maize plants. Application of H2O2 via soil varying from 0 to 320 µmol L-1 causes reductions in the CO2 assimilation rate and transpiration, as well as at concentrations from 0 to 160 µmol L-1 for stomatal conductance of plants irrigated with ECw of 2.0 dS m-1. Application of H2O2 via soil up to a concentration of 320 µmol L-1 increases the plant height, but reduces culm diameter of maize.